FOSTERING ACTIVE LEARNING THROUGH ART, TECHNOLOGY, AND OUTDOOR EDUCATION - Sriliza Sriliza; Ketty Nuramanda; Usna Usna; Aliya Aliya (CV. Adiba Aisha Amira, 2025)
This article discusses four innovative learning strategies: the use of interactive technology, outdoor learning, art-based learning, and differentiated instruction. The purpose of this study is to explore how these methods can enhance student engagement and learning outcomes in various educational settings. The research method used is a qualitative literature review based on credible academic sources. The findings indicate that interactive technology supports students in learning through digital interaction and visual simulations; outdoor learning provides real-world experiences that increase motivation; art-based learning encourages creativity and emotional expression; and differentiated instruction accommodates the diverse needs of students. These four strategies, when applied in a balanced and contextualized manner, can improve the quality of learning and promote a more inclusive classroom. The integration of these methods can also support teachers in creating a dynamic and responsive learning environment. The implications of this study highlight the importance of innovation and flexibility in modern pedagogy to meet the needs of 21st-century learners.